1991
DOI: 10.1128/aac.35.10.2078
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose pharmacokinetics of ceftibuten (SCH 39720) in infants and children

Abstract: Ceftibuten (CFB), a new broad-spectrum cephalosporin for oral administration, possesses potent activity in vitro against a wide range of gram-negative and certain gram-positive pathogens frequently encountered in pediatric patients. Its antimicrobial spectrum and dosage formulation suggest a use for CFB in the treatment of otitis media and upper and lower respiratory and urinary tract infections in infants and children. To assess the pharmacokinetic characteristics of CFB in pediatric patients, we completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Secondly, the mean V __ IF of ceftibuten in infants and children is also approximately 2-to 2.5-fold greater than corresponding values reported in adults with normal renal function (Kelloway et al 1991;Nakashima et al 1988a). Thirdly, the apparent CLNR for cis-ceftibuten in paediatric patients when expressed as a percentage of CLIF (52%) [Kearns et al 1991] appears to be higher than that in adults (32%) with creatinine clearances above 80 mllmin (4.8 Lib) [Kelloway et al 1991].…”
Section: Developmental Dependence In the Disposition Of Ceftibutenmentioning
confidence: 81%
See 3 more Smart Citations
“…Secondly, the mean V __ IF of ceftibuten in infants and children is also approximately 2-to 2.5-fold greater than corresponding values reported in adults with normal renal function (Kelloway et al 1991;Nakashima et al 1988a). Thirdly, the apparent CLNR for cis-ceftibuten in paediatric patients when expressed as a percentage of CLIF (52%) [Kearns et al 1991] appears to be higher than that in adults (32%) with creatinine clearances above 80 mllmin (4.8 Lib) [Kelloway et al 1991].…”
Section: Developmental Dependence In the Disposition Of Ceftibutenmentioning
confidence: 81%
“…Comparison of the pharmacokinetic data for ceftibuten in pediatric patients (Kearns et al 1991) with those previously reported from single-dose studies performed in healthy young adults (Kelloway et al 1991;Nakashima et al 1988a;Wise et al 1990) revealed potential developmental differences in the disposition of ceftibuten. First, the mean CLIF in children who are younger than 5 years of age is approximately 2.5-to 3.0-fold greater than values reported from adult studies (Kelloway et al 1991;Nakashima et al 1988a).…”
Section: Developmental Dependence In the Disposition Of Ceftibutenmentioning
confidence: 91%
See 2 more Smart Citations
“…Quantitation of ceftibuten in duplicate of both sc rum and bronchial secretion was performed by highperformance liquid chromatography (HPLC) accord ing to the method described by Kearns et al [14] with slight modifications. Samples (400 ml) were mixed with 20 ml of internal standard (acyclovir 100 mg/ml) and 600 ml of acetonitrile (Bracco, Milan, Italy).…”
Section: Ceftibuten Determinationmentioning
confidence: 99%